UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENGATASI MASALAH HUBUNGAN SOSIAL PESERTA DIDIK DI KELAS XI SMAN 4 PADANG - Elsya, Ulfah Nabila; Nita, Rahma Wira; Dianto, Mori (STKIP Pesisir Selatan, 2025)
This study aims to describe the efforts of Guidance and Counseling (BK) teachers in overcoming social relationship problems of students in class XI of SMA N Padang, which is motivated by the lack of optimal handling of these problems. The focus of the research includes the introduction of problematic students, understanding the types of problems, the implementation of assistance, and evaluation. Using a qualitative descriptive approach, this study involved 7 informants: 1 BK coordinator, 1 BK teacher, 3 students, 1 homeroom teacher, and 1 deputy principal. Data is collected through interviews and processed by data reduction, data presentation, and conclusion drawn. The results of the study show that BK teachers have made various efforts, including: 1) recognizing students with problems through observation and sociometry; 2) understand the types of problems such as social isolation and verbal bullying; 3) provide classical, group, and individual guidance services; and 4) conduct evaluations by building effective communication, practicing positive interactions, providing motivation to respect each other, and forming peer counselors. However, there are still students who are differentiated from friends and isolated. It is recommended that BK teachers conduct evaluations through individual counseling to practice positive interactions without discrimination, as well as homeroom teachers better understand and provide solutions to students' social relationship problems.